Forage Animal Feed Productivity in Bowi Subur Village, Masni District, Manokwari Regency, West Papua Province - Syaefullah, Bangkit Lutfiaji; Labatar, Susan Carolina; Timur, Ni Putu Vidia Tiara; Bachtiar, Ebit Eko (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2022)
ABSTRACT Forages are an integral part of ruminant production, therefore it is necessary to calculate the potential for forages at the ruminant farm. Aerial photo applications are used to make it easier to calculate forage land capacity and forage productivity. The objectives of this study were to determine the potential of the botanical composition of forages, calculate the capacity of forage land, and determine the productivity of forages. Based on the results of the study, mapping was carried out using satellite imagery in Bowi Subur Village, Masni District which has an area of 2,200 ha with a known forage area of 26,894.38 ha m-² with a production of 203,408.5 kg m-2 of fresh material and production dry matter of 61,755.61 kg m-2. The results of vegetation types in forages there are 22 types. Forage land in Bowi Subur Village has a fairly high diversity of vegetation. The type of vegetation with the highest percentage is weeds at 57.69%, grass with a percentage of 30.77%, and legume species with the lowest number at 11.53%. The low productivity of forages can result in livestock's low body weight because the forage's nutritional needs are not fulfilled optimally.Keywords:  forages, legumes, livestock, weeds